Mind in science : - Gregory, R. L. (Cambridge University Press, 1981)
This book is a jump from the academic mainstream and fascinates by a journey from the easliest recorded thinkers in the first known writing in Sumeria, through the gnomen (the Sumerian word for the finger on the sundial that measures time) to the knowledge and philosophy of Ancient Greece (they had cogwheels and gears) through classical times to the present. This is a history of science from a philosphical perspective, a reflection on the recorded mind of man. Richard Gregory is a philosopher, a scientist and a man who knows as much as anyone knows how the brain works. A tour de force, this book will change you by captivating and entertaining as well as profoundly altering your mind.